(untitled) (Research, Society and Development, 2021)
The definitive restauration of an endodontically treated tooth (ETT) is essential to prevent a possible periapical reinfection, which determines its short- and long-term prognosis. The aim of this paper is to determine the survival rate and the type of restoration that should be prescribed in posterior teeth according to the loss of tooth structure. In order to be able to achieve this, a search was conducted using digital databases such as: Cochrane, Scopus and PubMed using certain inclusion and exclusion criteria; as well as a manual search performed using Google Scholar. As a result, thirty-four articles were obtained for full reading, from which two classifications emerged, which allowed the reviewers to join criteria and propose a new classification which will make life easier for the reader at the time of choosing the ideal restoration. For those teeth with minimal loss of structure, the treatment of choice is composite restorations (91.9% to 100% rate of success); in teeth with a moderate loss of dental structure the ideal treatment was the use of indirect restorations of partial or total coverage (92.4% to 98.95 rate of success) alongside a fiber post if deemed necessary, finally, in teeth with a great loss of dental structure alternative techniques should be chosen in order to preserve as much dental tissue as possible. It is necessary to recognize the available options at the time of choosing a type of restoration according to the requirements of the tooth, always considering to be as conservative as possible so as not to further weaken its structure.